2009
DOI: 10.1164/rccm.200904-0501oc
|View full text |Cite
|
Sign up to set email alerts
|

[18F]Fluorodeoxyglucose Positron Emission Tomography for Lung Antiinflammatory Response Evaluation

Abstract: Rationale: Few noninvasive biomarkers for pulmonary inflammation are currently available that can assess the lung-specific response to antiinflammatory treatments. Positron emission tomography with [ 18 F]fluorodeoxyglucose (FDG-PET) is a promising new method that can be used to quantify pulmonary neutrophilic inflammation. Objectives: To evaluate the ability of FDG-PET to measure the pulmonary antiinflammatory effects of hydroxymethylglutarylcoenzyme A reductase inhibitors (statins) and recombinant human acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
56
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(61 citation statements)
references
References 29 publications
3
56
0
2
Order By: Relevance
“…Animal studies have shown that neutrophils are primary effectors of ''atelectrauma,'' (9, 32) and, in the setting of pulmonary inflammation, PET is a sensitive tool to detect the activation of these cells. Microautoradiography studies conducted both in animals (2,5,19,33) and in humans (20,21,34) suggest that uptake of 18 FDG occurs primarily by neutrophils. Furthermore, neutrophil depletion profoundly blunts the injury induced by mechanical ventilation (35) and the uptake of 18 FDG, albeit without abolishing it (3,36).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Animal studies have shown that neutrophils are primary effectors of ''atelectrauma,'' (9, 32) and, in the setting of pulmonary inflammation, PET is a sensitive tool to detect the activation of these cells. Microautoradiography studies conducted both in animals (2,5,19,33) and in humans (20,21,34) suggest that uptake of 18 FDG occurs primarily by neutrophils. Furthermore, neutrophil depletion profoundly blunts the injury induced by mechanical ventilation (35) and the uptake of 18 FDG, albeit without abolishing it (3,36).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, neutrophil depletion profoundly blunts the injury induced by mechanical ventilation (35) and the uptake of 18 FDG, albeit without abolishing it (3,36). Because the remaining signal could possibly arise from lung parenchymal cells, PET with 18 FDG is considered to provide a ''global'' measure of inflammatory response of the lung (21). The capability of PET to detect atelectrauma has been directly investigated in at least two studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 F]FDG PET has been applied to demonstrate anti-inflammatory effects of statin treatment after endotoxin-induced lung inflammation in volunteers (Chen et al, 2009 Cu-labeled peptide that targets the formyl peptide receptor on neutrophils (Zhang et al, 2007;Locke et al, 2009) (Fig. 3).…”
Section: Imaging In Respiratory Diseases: From Animal Models To Patientsmentioning
confidence: 99%
“…Reverse transcription was performed with the high-capacity cDNA reverse transcription kit (AB) in the presence of RNAse inhibitor (AB). The cDNA was then subjected to reverse transcription polymerase chain reaction (RT-PCR), using the [48] (370 kBq) was also used to evaluate the lung inflammation following the same endotoxin stimulation through biodistribution study with organs collected at 1 h p.i. [18].…”
Section: 411mentioning
confidence: 99%